Inceptions of biomathematics from Lotka to Thom. (1st March 2017) - Van Den Berg, Hugo
Mathematical biology occupies a special place at the interface between the physical, mathematical and life sciences. Is this interface merely a meeting point for dabblers venturing out of their own proper domains to work on problems of mutual interest? Or is it an incipient science in its own right, with its own particular character, principles, and practices? The past century has seen vast advances in the application of mathematical and physical ideas and techniques to biological problems, in the process transforming many of them almost beyond recognition. Nonetheless, the question of a biomathematics as a new kind of science remains open, despite several fascinating, if sometimes problematic, attempts.